Respon Pertumbuhan Kedelai (Glycine Max (L.) Merr.) Terhadap Cekaman Kekeringan - Pienyani Rosawanti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
Crop respotwes to drought stress depend on their gerctypes.The purpose of this research was to study the effect of drought stress the growth chqracters of soybean.research was conducted in the Cikabayan greenhouse-IPB using three genotypes of soybean (Slamet, Tanggamus and Wilis) and PEG (0%, 20%). The drought stress was applied only at a vegetative phose. The result showed that the interaction between genotype and PEG, significant. effect on root-shoot length ratio. Drought stress vtith PEG ;imulation causedthe changes in the growth characters of soybean i.e. on shoot length, root-lenght, root-shoot length ratio, leaf dry weight and root dry weight.